Manganese‐coated IRIS to document reducing soil conditions. Issue 6 (1st September 2021) - Rabenhorst, Martin C.; Drohan, Patrick J.; Galbraith, John M.; Moorberg, Colby; Spokas, Lesley; Stolt, Mark H.; Thompson, James A.; Turk, Judith; Vasilas, Bruce L.; Vaughan, Karen L.
Abstract: Iron‐coated indicatorof reduction in soils (IRIS) devices have been used for nearly two decades to help assess and document reducing conditions in soils, and official guidance has been approved for interpreting these data. Interest in manganese (Mn)‐coated IRIS devices has increased because Mn oxides are reduced under more moderately reducing conditions than iron (Fe) oxides (which require strongly reducing conditions), such that they are expected to be better proxies for some important ecosystem services like denitrification. However, only recently has the necessary technology become available to produce Mn‐coated IRIS, and the need is now emerging for guidance in interpreting data derived from Mn IRIS. Ninety‐six data sets collected over a 2‐yr period from 40 plots at 18 study sites among eight states were used to compare the performance of Mn‐coated IRIS with Fe‐coated IRIS and to assess the effect of duration of saturation and soil temperature as environmental drivers on the reduction and removal of the oxide coating. It appears that the current threshold prescribed by the National Technical Committee for Hydric Soils for Fe‐coated IRIS is appropriate for periods when soil temperatures are warmer (>11 °C), but is unnecessarily conservative when soil temperatures are cooler (5–11 °C). In contrast, Mn‐coated devices are particularly useful early in the growing season when soil temperatures are cool. Our data show that when using a threshold of 30% removal of Mn oxide coatings there is essentially 100% confidence of the presence of reducing soil conditions under cool (<11 °C) conditions. Core Ideas: Reduction of Fe and Mn oxides in soils is temperature dependent. Mn oxides are reduced faster and more easily than Fe oxides. At temperatures between 5–11 °C, removal of Fe oxides from IRIS is slow. The 30% threshold for Fe oxide removal from IRIS is appropriate when soil temperatures are >11 °C. A threshold of 30% removal for Mn‐coated IRIS is appropriate when soil temperatures are <11 °C.